Indonesian Female Writers’ Perspective Toward Acehnese Women: A Gynocritic Study - Herman Rusli; Maya Safhida; Nira Erdiana; Wildan Wildan (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2022)
This article is a study of the thoughts of Indonesian female writers towards Acehnese women as reflected in the literary works they produce. The objects used are the novel Perempuan Keumala by Endang Moerdopo (2008) and the novel Seulusoh by D. Kemalawati (2006). These two manuscripts were chosen because the background story used is about Aceh, the characters in the novel are Acehnese women. So far, it is difficult to find female Indonesian writers who highlight the social life of the female Acehnese in their stories. Thus, this study can be used as the basis for literary criticism in the field of Acehnese gynocritic feminism. This study uses a qualitative approach with descriptive text analysis. The theory that is used as the rationale for this study is Showalter's gynocritic literary criticism (1981 and 2000), which is now as a theory of contemporary literary criticism. The results of the analysis reflect the thoughts of Acehnese women writers on the figures of Acehnese women and Acehnese women in the view of women authors outside Aceh. The focus of the analysis includes (1) female biological elements; (2) female psychological elements; (3) female language; and (4) female culture. The results of the study show that Acehnese women in Acehnese women's literary works tend to appear as feminine figures, but are also brave, responsible, and have high social sensitivity. As for Acehnese women, in the eyes of women outside Aceh, they are described as brave, hard, responsible, and have a heroic spirit.